2016
DOI: 10.1177/1535370216654996
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipid deposition in farm animals: Parallels between agriculture and human physiology

Abstract: For many years, clinically oriented scientists and animal scientists have focused on lipid metabolism and fat deposition in various fat depots. While dealing with a common biology across species, the goals of biomedical and food animals lipid metabolism research differ in emphasis. In humans, mechanisms and regulation of fat synthesis, accumulation of fat in regional fat depots, lipid metabolism and dysmetabolism in adipose, liver and cardiac tissues have been investigated. Further, energy balance and weight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…We confirmed that human and pig lipoprotein profiles were similar and characterized by elevated LDL cholesterol compared to HDL cholesterol levels 13 . This is likely related to the physiological and anatomical similarities between both species 14 . With regard to rats and hamsters, similar lipoprotein profile analysis showed comparable distribution of cholesterol within HDL and LDL.…”
Section: Discussionmentioning
confidence: 89%
“…We confirmed that human and pig lipoprotein profiles were similar and characterized by elevated LDL cholesterol compared to HDL cholesterol levels 13 . This is likely related to the physiological and anatomical similarities between both species 14 . With regard to rats and hamsters, similar lipoprotein profile analysis showed comparable distribution of cholesterol within HDL and LDL.…”
Section: Discussionmentioning
confidence: 89%
“…To highlight the interest of developing the hepatic organoid model in these species, it is also necessary to identify the similarities and the differences and therefore to compare the hepatic metabolisms between the different species, including humans. If the metabolic pathways are generally very close, the nutritional lever is also used in domestic animals, in particular to control carbohydrate metabolism and lipidogenesis which does not take place exclusively in the liver for mammals with fat deposits in peripheral tissues [ 41 , 42 ].…”
Section: Applications In Other Speciesmentioning
confidence: 99%
“…Another example is the production of hepatic organoids from tissue biopsies in cats, to propose a model for studying NASH [ 46 ]. As previously mentioned, modeling this disease is still a challenge [ 36 ] and even if numerous rodent models are developed as well as in vivo assays on minipigs, few in vitro assays with organoids of mammalian domestic animals were presently reported [ 42 , 47 , 48 ].…”
Section: Applications In Other Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike cattle, humans accumulate intramuscular fat due to senescence and illness. Therefore, the marbling traits of Japanese Black cattle are considered a valuable research model for elucidating the molecular mechanism of ectopic intramuscular fat formation in various livestock, as well as in humans [5].…”
Section: Introductionmentioning
confidence: 99%